On the track of intramembrane clippers: the SPPL2a/b proteases caught in the act in animal models - Trávníčková, Květa; Stříšovský, Kvido (The FEBS journal, 2023)
In this issue, Ballin et al. report on their analysis of the substrate repertoire of SPPL2a and b intramembrane proteases. Based on the previous studies of their closest homologues, SPPL2c, SPPL3 and SPP, the authors hypothesized that SPPL2a/b proteases may cleave a subset of SNARE proteins. Indeed, four R-SNARE proteins, VAMP1, 2, 3 and 4, were cleaved by SPPL2a/b, both in overexpression assays and at endogenous levels. These findings have been validated by analysis of SPPL2a/b double knock-out mice tissues, which implicates these proteases in the regulation of SNARE protein turnover in vivo. The study of Ballin et al. also provides material for future studies of factors determining substrate specificity of SPPLs, as they cleave different subsets of the tail-anchored SNARE proteins. Comment on: https://doi.org/10.1111/febs.16610.
Keywords: proteolýza; sekretasy; Mice; Proteolysis; Models, Animal; Membrane Proteins; membránové proteiny; Amyloid Precursor Protein Secretases; Animals; aspartátové endopeptidasy; modely u zvířat; zvířata; Aspartic Acid Endopeptidases; myši